2021
DOI: 10.1002/mds.28740
|View full text |Cite
|
Sign up to set email alerts
|

Gait Variability in Spinocerebellar Ataxia Assessed Using Wearable Inertial Sensors

Abstract: A BS TRACT: Background: Quantitative assessment of severity of ataxia-specific gait impairments from wearable technology could provide sensitive performance outcome measures with high face validity to power clinical trials. Objectives: The aim of this study was to identify a set of gait measures from body-worn inertial sensors that best discriminate between people with prodromal or manifest spinocerebellar ataxia (SCA) and age-matched, healthy control subjects (HC) and determine how these measures relate to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 54 publications
3
50
0
Order By: Relevance
“…Measures describing the variability of gait pattern have proven cross-sectional sensitivity to ataxia severity in a wide range of recording methods 30, 31 including marker-based capturing systems as gold standard 9, 10, 21 , gait mattresses 13, 20 , wearable inertial sensors 4, 5, 7, 8 , and camera-based systems 6 like the multi-kinect system 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measures describing the variability of gait pattern have proven cross-sectional sensitivity to ataxia severity in a wide range of recording methods 30, 31 including marker-based capturing systems as gold standard 9, 10, 21 , gait mattresses 13, 20 , wearable inertial sensors 4, 5, 7, 8 , and camera-based systems 6 like the multi-kinect system 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, larger future studies are needed, including in particular a higher number of pre-ataxic subjects, to further validate the promises of gait measures. In future multi-center studies, the gait measures identified here might also be assessed not by a stationary analysis set-up, but rather by wearable inertial sensors 4, 5, 8 , which would -as important for ecological relevance-also allow assessments of these measures in patients’ real life 4, 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wearable sensors with inertial measurement units (IMU) that contain triaxial accelerometers have been used in A-T and other pediatric ataxias to measure aspects of limb motor impairment during in-clinic administered tasks [ 12 – 15 ]. Multi-sensor IMU systems have been successfully used both inside [ 16 – 19 ] and outside [ 20 ] the clinic to quantify gait impairments in different ataxias. These are promising technologies for objective quantification of motor impairment but have limitations in that they are not applicable across all ages and are not designed to accommodate frequent, at-home use in children.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their broad availability and the convenient option to implement applications, they may provide an attractive hands-on tool for measuring gait and balance in home-based settings. However, this set-up has been applied only recently in the field of motion analyses [10,11] and is not yet part of the standard clinical tools of measuring gait and balance.…”
Section: Introductionmentioning
confidence: 99%